Інформаційні ресурси інтерактивної системи підтримки рішень з питань управління екологічною безпекою українського сектору Чорного моря - Красовський, Г.Я.; Радчук, В.В.; Загородил, С.А. (Геоінформатика, 2016)
Визначено структуру і зміст геоінформаційних ресурсів інтерактивної системи підтримки рішень з питань управління екологічною безпекою територіальних вод України в Чорному морі. Ці ресурси ґрунтуються на методах тематичного дешифрування космічних знімків повної лінійки розрізнення та технологіях геоінформаційних систем. Определены структура и содержание геоинформационных ресурсов интерактивной системы поддержки решений по вопросам управления экологической безопасностью территориальных вод Украины в Черном море. Эти ресурсы базируются на методах тематического дешифрирования космических снимков полной линейки различия и технологиях геоинформационных систем. Purpose. An interactive system proves to allow us to put into practice the concept of centralized processes of data collection, systematization, accumulation and storage, as well as providing the interested user with primary data for information support of decision-making related to protection and effective use of renewable natural resources of the coastal land and sea areas. In addition, can enable regional authorities to operate much more effectively in decision grounding, planning and making since it permits to remove duplication of essential primary environmental data searching processes and ensures their rapid updating. It should be noted that remote sensing technologies for sea areas, along with geoinformation tools, allow us to get current information of high accuracy and good visual presentation. The above permits to obtain quantitative estimation of sea pollution of catastrophic proportion and to identify coastal sites in terms of decision-making related to prioritizing remedial actions. Also, there is a significant social, environmental and economic effect due to the economy of time and human and financial resources.
Design/methodology/approach. The major advantage of the sea water areas remote sensing methods is that they ensure: high observability, possibilities of getting instantaneous information on large sites of sea water areas; possibility of moving from discrete valuation of the sea waters environmental state in certain selected areas to identification of their infinite spatiotemporal distribution; possibility of identifying environmental state of distant sea sites. It makes sense to integrate the above methods with geoinformation technologies within the structure of an interactive decision-making support system with regard to environmental safety management issues in the Ukrainian sector of the Black Sea. The present article is devoted to identifying informational resources for this system.
Findings. Modern geoinformation systems offer new opportunities for the above results to be generalized because they provide for geospatial data management and allow: to create cartographic images of the sea sites with the given types of connections between information and data bases of technical-and-economic parameters of discharge sources into the sea outfall; to present dynamics of the current sea waters pollution levels and predict the speed and tendencies of their spreading; to visualize sea sites state characteristics in the form of thematic maps on a topographic full scope basis.
Practical value/implications. Practical implication of the results from environment-oriented interpretation of space images increases when they are analyzed together with assessment of environmental components state made using contact methods.
The above peculiarities of ERS and GIS permit to discover previously unknown characteristics, interrelations and tendencies in the environmental state particular sea sites. The article presents cartographic models of environmental state of the Black Sea offshore strip constructed by means of thematic decoding of space images. Of specific interest are models obtained in NOAA processing of images that are received in real timing by the space image receiving station of the National Aerospace University “Kharkiv Aviation Institute”.